Dopamine and Opioid Neurotransmission in Behavioral Addictions: A Comparative PET Study in Pathological Gambling and Binge Eating - Majuri, Joonas; Joutsa, Juho; Johansson, Jarkko; Voon, Valerie; Alakurtti, Kati; Parkkola, Riitta; Lahti, Tuuli; Alho, Hannu; Hirvonen, Jussi; Arponen, Eveliina; Forsback, Sarita; Kaasinen, Valtteri (Neuropsychopharmacology (New York, N.Y.), 2017)
Although behavioral addictions share many clinical features with drug addictions, they show strikingly large variation in their behavioral phenotypes (such as in uncontrollable gambling or eating). Neurotransmitter function in behavioral addictions is poorly understood, but has important implications in understanding its relationship with substance use disorders and underlying mechanisms of therapeutic efficacy. Here, we compare opioid and dopamine function between two behavioral addiction phenotypes: pathological gambling (PG) and binge eating disorder (BED). Thirty-nine participants (15 PG, 7 BED, and 17 controls) were scanned with [ C]carfentanil and [ F]fluorodopa positron emission tomography using a high-resolution scanner. Binding potentials relative to non-displaceable binding (BP ) for [ C]carfentanil and influx rate constant (K ) values for [ F]fluorodopa were analyzed with region-of-interest and whole-brain voxel-by-voxel analyses. BED subjects showed widespread reductions in [ C]carfentanil BP in multiple subcortical and cortical brain regions and in striatal [ F]fluorodopa K compared with controls. In PG patients, [ C]carfentanil BP was reduced in the anterior cingulate with no differences in [ F]fluorodopa K compared with controls. In the nucleus accumbens, a key region involved in reward processing, [ C]Carfentanil BP was 30-34% lower and [ F]fluorodopa K was 20% lower in BED compared with PG and controls (p<0.002). BED and PG are thus dissociable as a function of dopaminergic and opioidergic neurotransmission. Compared with PG, BED patients show widespread losses of mu-opioid receptor availability together with presynaptic dopaminergic defects. These findings highlight the heterogeneity underlying the subtypes of addiction and indicate differential mechanisms in the expression of pathological behaviors and responses to treatment.